Pengembangan Modul IPA Berkarakter Terintegrasi Nilai-Nilai Islam untuk Meningkatkan Sikap Spiritual Peserta Didik SMP/MTs - Muchlis Muchlis; Magfirah Perkasa; Muhammad Irwansyah; Ariyansyah Ariyansyah (JURNAL PENDIDIKAN MIPA, 2020)
National education system aims to produce students who have intact intelligence, be it intellectual intelligence, emotional intelligence, spiritual intelligence and social intelligence. But the facts in the field say differently. Spiritual and social intelligence tends to be overlooked by educators in schools. Therefore, this research was carried out with the aim of producing a science module with an integrated character of Islamic values to improve students' spiritual attitudes or those that meet valid and effective criteria. This type of research is development research that follows the stages of Thiagarajan development which consists of the stages of defining, designing, developing and disseminating. The instruments used were validation sheets and student response questionnaires. Based on the results of limited trials, it can be concluded that the science module with the character of integrated Islamic values meets the criteria of validity and effectiveness. Hopefully the results of this research can be used as a reference in improving the quality of education in Indonesia, especially in Bima City, West Nusa Tenggara Province.